Risk Factors for Recurrent Obstetric Anal Sphincter Injury (rOASI): A Systematic Review and Meta-analysis. Issue 9 (September 2016) - Jha, Swati; Parker, Victoria
Abstract : (Abstracted from Int Urogynecol J 2016;27:849–857) Recent surveys have shown that the incidence of obstetric anal sphincter injury (OASI) is rising with rates ranging from 0% to 8% across the world. Obstetric anal sphincter injury causes many concerns related to fecal incontinence, perineal pain, dyspareunia, psychological problems such as depression, and has an overall impact on quality of life, at times being a factor that deters women from having another child.